The Influence of Celebrity Endorsement and Product Quality on Online Shopping Interest - Syifa Fauziah Hamidah (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2021)
The development of online shopping in Indonesia is very fast than offline shopping makes promotion online also great demand, one form of online promotion is a promotion to an online celebrity who is considered to influence online sales. The purpose of this study is to determine how celebrity endorsement, product quality, and interest in buying online shopping case study students in the city of Bandung and to find out how much influence celebrity endorsement has on buying interest in online shopping, the effect of product quality on buying interest in online shopping, and the effect of celebrity endorsement and product quality on buying interest in online shopping. This study is a sample study in which consumers are respondents in the study, for data collection using a questionnaire with several respondents 200 people. The analytical method used is a quantitative method with descriptive analysis and verification analysis. To process data, the authors use the help of Microsoft Excel 2013 and SPSS 25 For Windows. The endorsement is in a good category, product quality is in a good category, and buying interest is in a good category. The results of this study either partially or simultaneously celebrity endorsement and product quality have a positive effect on buying interest in online shopping.